The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0103-21002007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa multiresistente em unidade de cuidados intensivos: desafios que procedem?

Abstract: OBJETIVOS: Avaliar a ocorrência de infecção hospitalar por Pseudomonas aeruginosa multiresistente em pacientes hospitalizados em uma unidade de cuidados intensivos. MÉTODO: estudo retrospectivo realizado de outubro de 2003 a setembro de 2004 em um hospital de emergências. RESULTADOS: Totalizou-se 68 portadores de bactérias multiresistentes sendo 10 (14,7%) de P. aeruginosa. Destes, 8 pacientes eram do sexo masculino, as médias de idade e de internação foram respectivamente de 57 anos a média de idade, 43,7 a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
1
0
9
Order By: Relevance
“…A study [44] reported the presence of MDR Enterobacteria in 22.2% of 18 sampled surfaces, which is consistent with our findings (19.44%) for the AICU of Hospital A. European data [45] showed a high level of contamination by P. aeruginosa in sink isolates and tap biofilms. In line with this, our study recovered P. aeruginosa from 25% of sink samples, which attests that this pathogen is commonly associated with humid sites in the hospital environment and is the main microorganism isolated in ICUs [46]. In contrast, from a total of seventeen P. aeruginosa isolates found in this study, eleven were non-MDR isolates from door knobs of the ER, which is not a humid environment.…”
Section: Discussionsupporting
confidence: 84%
“…A study [44] reported the presence of MDR Enterobacteria in 22.2% of 18 sampled surfaces, which is consistent with our findings (19.44%) for the AICU of Hospital A. European data [45] showed a high level of contamination by P. aeruginosa in sink isolates and tap biofilms. In line with this, our study recovered P. aeruginosa from 25% of sink samples, which attests that this pathogen is commonly associated with humid sites in the hospital environment and is the main microorganism isolated in ICUs [46]. In contrast, from a total of seventeen P. aeruginosa isolates found in this study, eleven were non-MDR isolates from door knobs of the ER, which is not a humid environment.…”
Section: Discussionsupporting
confidence: 84%
“…Com isso, pode-se perceber que a maioria das amostras foi isolada a partir do material do trato respiratório (68%). Esse fato também foi constatado por Menezes et al (26) , o que de certa forma já era esperado, uma vez que relatamos, em nosso estudo, grande quantidade de cepas isoladas de Pseudomonas aeruginosa, microrganismo comum em patologias respiratórias (13,15,35) . Estudando esse patógeno, encontramos a maioria de cepas provindas do trato respiratório.…”
Section: Figura -Perfil De Resistência Aos Antimicrobianos De Pacientunclassified
“…e 0 r, resulting in approximately 300,000 deaths (Ferrareze et al, 2007). The risk of nosocomial infection is related to the patient's length of stay in hospital, the patient's immunological and nutritional status, patient's age, the use of immunosuppressants and antibiotics and invasive procedures (Ferrareze et al, 2007;Santos, 2004).…”
mentioning
confidence: 99%